Recreational Activities Program as a Complimentary to Hotel Guests - Ni Luh Putu Sri Sartika Wati; Lien Darlina; I Gusti Agung Mas Krisna Komala Sari; Ni Made Ernawati; Ni Made Rai Sukmawati; Ni Wayan Wahyu Astuti (The Postgraduate School of Tourism Sahid Polytechnic, 2022)
ABSTRACT Purpose: The purpose of this study was to determine the interest of guests in the recreation activities program as a complimentary to guests staying at a 5-star hotel in Ungasan, Bali, Indonesia, and to find out which recreation activities were most in demand by guests at the hotel. Research methods: Data collection methods used are observation, interviews, and documentation. The data analysis technique used is descriptive qualitative analysis technique and descriptive statistics. Results and discussion: The study shows that the TTH (The Tree House) Activities that were most attractive to guests in 2019 were art & craft (5.48%), painting (5.40%), nature painting (4.68%), learning Balinese (4.46%), Balinese dance (4, 46%). The year 2020 is a temple tour (4.77%), hotel tour (4.72%), clay making (4.31%), painting and gardening (4.19% each), and music class (3.91 %). Implication: The guests’ interest in the recreation activities program is very good, which can be seen in the percentage of guests participating in the recreation activities program of 35.8% of the total number of guests at the hotel in 2019 and 2020. Keywords: recreation activities, interested activities, spa & recreation department.